Kajian Kohesi pada Cerpen “Dalam Perjamuan Cinta” Karya Taufiq El-Hakim - Mujahid Taha (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
This paper aims to identify and determine the use of the elements of cohesion in the shortstory “dalam Perjamuan Cinta” (DPC). The method used is descriptive qualitative methodusing two approaches in discourse, namely the principle of analogy and local principles.The results showed that the appearances of the elements of grammatical cohesion in this reference are demonstrative pronouns and pronominal singular persona is more often foundin every temple of the fictional discourse paragraphs compared with lexical cohesion.